PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA GURU DI SMP TAMAN SISWA PEMATANGSIANTAR - Putra, Hendrick Sasimtan; Candra, Vivi; Putri, Debi Eka; Hanum, Farida (Universitas Mahendradatta Denpasar, 2025)
This study aims to analyze the representation of Organizational Citizenship Behavior (OCB) and teacher performance at SMP Taman Siswa Pematangsiantar, as well as evaluate the influence of OCB on teacher performance. The research employs a quantitative design with a descriptive approach through literature and field studies, involving a population of 24 individuals. Data were collected through questionnaires, interviews, and documentation, and analyzed using normality tests, descriptive analysis, and quantitative analysis. The results indicate that OCB and teacher performance are categorized as good. Furthermore, it was found that OCB has a positive and significant influence on teacher performance. The relationship between OCB and teacher performance is strong, with OCB making a significant contribution to explaining the teacher performance variable. These findings highlight the strategic role of OCB in enhancing teacher performance, making the optimization of OCB a crucial factor in improving the quality of education.